ANALISIS KEBIJAKAN PRIVATISASI PADA BUMN YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2000-2011 - Putri, Anggi Arinta; Sunarko, Bambang; Suwaryo, Suwaryo (Performance, 2013)
The aim of Privatization Policy is to improve performance and value added of BUMN. This research analyze, is there differentiation of financial performance in BUMN before and after privatization. The test used 8 distinguishing variable according to Minister Decree No: KEP-100/ MBU/2002. This research used purposive sampling method and Paired Sample T-test to analyze the hypothesis. The research gives empirical findings that there was no significant difference from ROI, Cash Ratio, Collection Period, Inventory Turnover, and Total Equity to Total Assets whereas ROE, Current Ratio, and Total Asset Turnover were significantly different in BUMN after privatization.